Sebaceous gland receptors - Zouboulis, Christos C (Landes Bioscience, 2009)
Receptors are proteins, embedded in a cell or cytoplasmic membrane, to which a mobile signaling molecule may attach. Receptor ligands may be peptides (such as neurotransmitters), hormones, pharmaceutical drugs and/or a toxins, whereas “binding” ordinarily initiates a cellular response. Human sebocytes are biologically and metabolically very active cells and consequently express numerous receptors. Three of four groups of peptide/neurotransmitter receptors, the so-called serpentine receptor group are present (corticotropin-releasing hormone receptors 1 and 2, melanocortin-1 and 5 receptors, μ-opiate receptors, VPAC receptors, cannabinoid receptors 1 and 2, vascular endothelial growth factor receptor and histamine 1 receptor). The single-transmembrane domain receptors are represented by the insulin-like growth factor-I receptor and the third group, which does not possess intrinsic tyrosine kinase activity, by the growth factor receptor. Nuclear receptors expressed in sebocytes are grouped into two major subtypes. From the steroid receptor family, the androgen receptor and the progesterone receptor are expressed. The thyroid receptor family includes the estrogen receptors (α and β isotypes), the retinoic acid receptors (isotypes α and γ) and retinoid X receptors (isotypes α, β, γ), the vitamin D receptor, the peroxisome proliferator-activated receptors (isotypes α, δ and γ) and the liver X receptors (α and β isotypes). The vanilloid receptor belongs to the transient ion channels and is expressed in differentiating human sebocytes. Further sebocyte receptors, which may influence their function are fibroblast growth factor receptor 2, epidermal growth factor receptor, c-MET, CD14, Toll-like receptor 2, Toll-like receptor 4 and Toll-like receptor 6. Receptor-ligand interactions control sebocyte proliferation, differentiation and lipid synthesis. However, not every ligand that binds to a sebocyte receptor also activates it, such ligands are receptor antagonists and inverse agonists.